A supply chain analysis of the mussel industry in Jiabong, Samar. - Abarracoso, Tessie A.; Pabunan, Joanne B.; Tagoctoc, Vanessa T. (Tacloban City Tessie A. Abarracoso, Joanne B. Pabunan, 2019)
The municipality of Jiabong is known for its green mussels, Perna viridis (Linnaeus, 1758). It is the top supplier of mussels in the region, making it the Mussel Capital of Eastern Visayas and the major source of livelihood for the people of Jiabong since the 1970s.
The primary goal of this paper was to lay out the different stages of activities in the mussel industry by using a Supply Chain Analysis. Data were collected from the 88 respondents from Brgy. Alejandrea and Jia-an, Jiabong, Samar. Results showed that the customary method used in preparation stage was staking which was estimated to last at an average of 3-5 hours. Mussels were freshly sold directly to its buyers, who usually sets the price, and most of the mussel produce were supplied to markets of Jiabong, Catbalogan, Manila and Davao. Problems encountered by the respondents include red tide, unfavorable weather, illegal fishing, theft and finance. Most of the respondents did not receive any assistance, such as calamity funds, from the NGOs and government agencies. Although there exists an association of mussel producers under the supervision of BFAR, some respondents were not able to avail the said assistance. The industry had its own potential as it provides employment, and the increase supply of mussels contributes to the food security inside and outside the community. Moreover, the role of the LGU and other government agencies is to have an active participation and support towards a more productive and successful mussel industry. Lastly, further researches are encouraged for a better understanding of the mussel industry in Jiabong, especially on the other stages of its supply chain. Value chain analysis is recommended to further determine the additional values on enhanced raw products, such as tahong crackers and bottled tahongs.
Undergraduate thesis (B.A. Psychology) -- University of the Philippines, Tacloban.